The compartmentalization and biomarker analysis of the spivey-grabs-basil field, south-central Kansas - Evans, Drew W. (Kansas State University, 2011)
The Spivey-Grabs-Basil oil field is a highly developed field in south-central Kansas, having large variability in its production and in the Pineville Tripolite facies. The Pineville Tripolite is the primary producing formation of this field having major isopach variations, possibly influencing production. The hypothesis that the field is highly compartmentalized is from the varied production, isopach and structure of the field. This study investigated the Pineville Tripolite facies in the Spivey-Grabs-Basil Oil Field, with the Basil area the predominant focus, and its possible compartmentalization by looking at the gas chromatograms and their biomarker signatures. This field has had several studies investigating the geophysical attributes, depositional setting and large-scale compartmentalization. Post depositional sea-level changes and possibly syntectonics exposed the Reeds Spring to a sub-aerial environment where meteoric alteration created immense porosity and the Pineville Tripolite facies. Geochemical data shows evidence that this section of the field is sourced from both a marine shale and carbonate source at peak oil maturity, deposited in an anoxic environment. Biodegradation appears very slight, with most alterations transpiring in the alkane ranges only, leaving all other susceptible hydrocarbons unaltered. Compartments within the field are harder to identify when comparing geological data to oil data. Isopach data shows altered thickness of the Pineville Tripolite from well to well, as do Pineville structure values. The isopach and structural data point to possible areas for compartments, but it is from oil geochemical data that compartments become more visible. API gravities and GOR show motley values, but do indicate two significant areas of segregation. The deepest, most southern end of the study showed lighter gravity oils than the middle, suggesting possible fill and spill between the two. However, biomarker abundance indicates three possible compartments. The southern compartment has many more biomarker volumes than do the middle compartment, both divided by a reservoir pinch-out. The third most northeastern well has high biomarker abundance, but shows no geological separators from the other wells. Production from this field may be improved by investigating the biomarkers to allocate these compartments and possible barriers close to wells.
Keywords: Compartmentalization; Biomarkers; Geology; Geochemistry; Geochemistry (0996); Geology (0372)